Recent advances in metal-organic frameworks for anticancer nanodrug delivery - Subedi, Anup; Basnet, Bikram Bdr; Karki, Ravi (Himalayan Physics, 2025)
Cancer is a leading cause of death in the 21st century. It results from the uncontrolled growth of cells that disrupt normal organ function. Traditional treatments like radiotherapy, chemotherapy, and surgery are commonly used. These can damage healthy cells and cause unwanted side effects. Metal-organic frameworks (MOFs) have emerged as an innovative solution in cancer therapy. They offer advancements in drug delivery systems. MOFs have unique properties, including high surface area, tunable structures, and the ability to encapsulate various therapeutic agents. They provide more efficient, targeted, and controlled drug delivery. The selective targeting capabilities of MOFs allow for direct treatment of cancer cells. This minimizes damage to healthy tissue and reduces adverse effects of conventional therapies. While MOFs hold great potential in cancer treatment, challenges remain. These include scalability, stability, bio-compatibility, and safety in clinical settings. Ongoing research is focused on overcoming these challenges. With further advancements, MOFs could revolutionize cancer treatment. They offer safer, more effective alternatives to current therapies, improving patient outcomes.